2020
DOI: 10.1177/1945892420920499
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Allergic Rhinitis and Associated Risk Factors in 6 to 12 Years Schoolchildren From Wuhan in Central China: A Cross-sectional Study

Abstract: Background Over the past decade, the prevalence of allergic rhinitis (AR) in China increased and showed a trend of younger age. The clinical features of AR in primary schoolchildren are still not clear enough. Objective To investigate the prevalence and epidemiological characteristics of AR among 6- to 12-year-old children in the central region of China. Methods Children from 6 primary schools were randomly selected from urban area of Wuhan, which lies in the central region of China. The questionnaires were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Atopic sensitization was investigated by specific IgE tests in nine studies (6,12,27,(29)(30)(31)34,38,46) . Seventeen out of 23 studies had adequate adjustment for confounding variables (6,12,27,28,(30)(31)(32)(33)(34)(35)(36)(40)(41)(42)(43)(44)46) .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Atopic sensitization was investigated by specific IgE tests in nine studies (6,12,27,(29)(30)(31)34,38,46) . Seventeen out of 23 studies had adequate adjustment for confounding variables (6,12,27,28,(30)(31)(32)(33)(34)(35)(36)(40)(41)(42)(43)(44)46) .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eighteen studies assessed the effect of prolonged nonexclusive breastfeeding (≥6 months) (6,12,26,28,29,(31)(32)(33)(34)(35)(36)(39)(40)(41)(42)(43)(44)46) . One study (33) used hazard ratio (HR) and found no association with the risk of seasonal AR.…”
Section: Nonexclusive Breastfeeding ≥6 Months and Its Impact On The Development Of Armentioning
confidence: 99%
See 2 more Smart Citations
“…Although the precise mechanism of this change is not known, it is thought that the C-to-T transition causes an aberrant overexpression of TGFB1, resulting in elevated IgE levels, tissue remodeling and fibrosis. In another Chinese study of school children in the Wuhan province, Tong et al 2 demonstrates a higher prevalence of AR (27%) than previously-reported population data. This study impressively collected cross-sectional data from over 5500 students, revealing several positive risk factors for the development of disease, including male gender, living in an urban setting, and frequent exposure to antibiotics.…”
mentioning
confidence: 74%